Advances in magnetic nanoparticles for biomedical applications - Cardoso, Vanessa Fernandes (2018)
Magnetic nanoparticles (NPs) are emerging as an important class of biomedical functional nanomaterials in areas such as hyperthermia, drug release, tissue engineering, theranostic, and lab-on-a-chip, due to their exclusive chemical and physical properties. Although some works can be found reviewing the main application of magnetic NPs in the area of biomedical engineering, recent and intense progress on magnetic nanoparticle research, from synthesis to surface functionalization strategies, demands for a work that includes, summarizes, and debates current directions and ongoing advancements in this research field. Thus, the present work addresses the structure, synthesis, properties, and the incorporation of magnetic NPs in nanocomposites, highlighting the most relevant effects of the synthesis on the magnetic and structural properties of the magnetic NPs and how these effects limit their utilization in the biomedical area. Furthermore, this review next focuses on the application of magnetic NPs on the biomedical field. Finally, a discussion of the main challenges and an outlook of the future developments in the use of magnetic NPs for advanced biomedical applications are critically provided.